Last sacrifice - Mead, Richelle (London : Penguin Books, 2013)
After a devastating betrayal, Rose and Lissa's friendship is destroyed as Rose stands trial and Lissa becomes the first in line for the Royal Crown.
Young Adult.
Young Adult
Keywords: Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; Vampires -- Juvenile fiction; Friendship -- Fiction; High schools -- Fiction; Magic -- Fiction; Schools -- Fiction; Vampires -- Fiction; High schools -- Fiction; Magic -- Fiction; Occult fiction; School stories; Vampires -- Fiction; Occult fiction